Bone regeneration with bovine bone impairs orthodontic tooth movement despite proper osseous wound healing in a novel mouse model. Issue 2 (27th September 2018) - Klein, Yehuda; Fleissig, Omer; Stabholz, Ayala; Chaushu, Stella; Polak, David
Abstract: Background: The aim of this study was to investigate the biological mechanisms underlying alveolar bone regeneration (ABR) and orthodontic tooth movement into bovine bone (BB) regenerated sites. Methods: Two mouse models were established in C57BL/6 mice. The ABR model was based on osseous defects filled with BB. The orthodontic tooth movement‐ABR model was used to move a molar into the regenerated site. Osseous morphometric analysis and tooth movement distance were evaluated with micro‐CT. Histologic characteristics and osteoclast (OCS) accumulation were evaluated by hematoxylin and eosin and tartrate‐resistant acid phosphatase staining (TRAP). Expression and location of the receptor activator of nuclear factor‐kappa B (RANKL) and of osteoprotegerin (OPG) were evaluated by immunofluorescent staining. Results: Bone healing peaked at 4 weeks. The distance of the orthodontic tooth movement into the bovine bone was significantly reduced versus that of the nonbovine bone controls. BB particles accumulated along the root's pressure side during orthodontic treatment. Despite the osteoclasts' presence adjacent to the BB particles, no BB resorption was observed. Increased RANKL expression was seen at the orthodontic tooth movement pressure zone, without any change in OPG expression. Conclusion: The two novel mouse models show that the lack of resorption of BB xenografts renders them inadequate for proper orthodontic tooth movement at a later stage.